2003
DOI: 10.1345/aph.1c267
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist Intervention Program for Control of Hypertension

Abstract: Pharmacist intervention can modify factors affecting adherence, improve adherence, and reduce BP levels in patients treated with antihypertensive agents. Impact of pharmacist intervention on BP differed according to patient income status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(112 citation statements)
references
References 18 publications
(14 reference statements)
5
100
0
3
Order By: Relevance
“…Although, this problem cannot be completely solved, there will be a cost-effective solution provided by clinical pharmacist to those patients according to their existing conditions. Some reports also indicated that pharmacist interventions were not likely to gain a statistically significant improvement in this outcome when medication adherence at baseline is already high (about 75%) (Chabot et al, 2003;Jokisalo et al, 2003), and in our study, low baseline medication adherence (47.5%) made it feasible for pharmaceutical intervention to get an obvious positive effect in this outcome and hence in treatment outcomes. And in the end, our percentage of low medication adherence accounted for 24.8%, which perfectly matched that in other studies.…”
Section: Discussionsupporting
confidence: 42%
“…Although, this problem cannot be completely solved, there will be a cost-effective solution provided by clinical pharmacist to those patients according to their existing conditions. Some reports also indicated that pharmacist interventions were not likely to gain a statistically significant improvement in this outcome when medication adherence at baseline is already high (about 75%) (Chabot et al, 2003;Jokisalo et al, 2003), and in our study, low baseline medication adherence (47.5%) made it feasible for pharmaceutical intervention to get an obvious positive effect in this outcome and hence in treatment outcomes. And in the end, our percentage of low medication adherence accounted for 24.8%, which perfectly matched that in other studies.…”
Section: Discussionsupporting
confidence: 42%
“…The majority have been shown to improve outcomes in hypertension, by improving adherence and reducing BP levels. Nevertheless, a study 39 showed that the impact of such a pharmacist intervention is largely conditioned by patients' income status: the low-income group did not appear to benefit from the programme. These programmes are not only effective, but also efficient: a programme, 40 which consisted in the pharmacist measuring and recording the patient's BP and assessing adherence to drug treatment each time the patient came to the pharmacy to refill his/ her antihypertensive medication, showed benefits of about 10 times higher than costs.…”
Section: Self-bp Measurementmentioning
confidence: 99%
“…2 In several published studies, pharmacists have been shown to improve care for patients with cardiovascular disease, notably patients with hypertension. [3][4][5][6][7] In order to prepare students for clinical practice, colleges and schools of pharmacy are tasked with teaching about the management of hypertension as well as fostering the skill of blood pressure assessment.…”
Section: Introductionmentioning
confidence: 99%